Chemogenetic activation of Gq signaling modulates dendritic development of cortical neurons in a time- and layer-specific manner - Köhler, Ina; Rennau, Lisa Marie; Rehm, Adriana; Große, Julia; Gonda, Steffen; Räk, Andrea; Riedel, Christian; Wahle, Petra (Frontiers in Cellular Neuroscience, 2025)
Designer receptors exclusively activated by designer drugs (DREADDs) are established tools for modulating neuronal activity. Calcium-mobilizing DREADD hM3Dq has been widely used to enhance neuronal activity. hM3Dq activates the Gq protein signaling cascade and mimics the action of native Gq protein-coupled receptors such as muscarinic m1 and m3 receptors leading to calcium release from intracellular storages. Depolarization evoked by increased intracellular calcium levels is an important factor for neuronal maturation. Here, we used repetitive activation of biolistically overexpressed hM3Dq to increase the activity of individual neurons differentiating in organotypic slice cultures of rat visual cortex. HM3Dq was activated by 3 μM clozapine-N-oxide (CNO) dissolved in H2O. Transfectants expressing hM3Dq mock-stimulated with H2O served as batch-internal controls. Pyramidal cells and multipolar interneurons were analyzed after treatment from DIV 5–10, DIV 10–20, and DIV 15–20 to investigate if Gq signaling is involved in dendritic maturation. Results show that hM3Dq activation accelerated the maturation of apical dendrites of L2/3 pyramidal cells in the early, but no longer in the later time windows. In contrast, dendritic dimensions of L5/6 pyramidal cells and interneurons were not altered at DIV 10. These findings suggest a growth-promoting role of activated Gq signaling selectively for early postnatal L2/3 pyramidal cells. Unexpectedly, hM3Dq activation from DIV 10–20 reduced the dendritic complexity of L5/6 pyramidal cells and multipolar interneurons. Together, results suggest a role of Gq signaling for neuronal differentiation and support evidence that it may also limit dendritic growth.